Material flow analysis of white bread production: Case study at a home-scale bakery production in Surabaya - Sar Manik, Yosef Barita; Radia, Sabrina Alia; Putri, Nurul Ayanda; Azwar, Arrizal; Amaral, Joaozinho Jubileu San Sao (Journal of Tropical AgriFood, 2026)
Bread production in urban areas of Indonesia requires significant resource inputs (total 150 kg: 85.21 kg flour, water 52.33 kg, sugar 4.26 kg, salt/yeast 1.74 kg each, oil 1.40 kg, butter 1.32 kg, eggs 2.00 kg for 135 kg/day of bread ready for distribution) while also producing solid waste and emissions, thus requiring an efficiency assessment through Material Flow Analysis (MFA) for sustainability. This study applied MFA with a gate-to-gate approach to seven operational units: weighing, mixing, fermentation, dough forming, baking, cooling, and packaging at a home industry in Surabaya, using primary data from structured interviews (October 29, 2025) and secondary data from literature. The results show high efficiency with a Product Yield of 90%, Organic Waste of 3.34%, NPOR (Non-Product Output Ratio) of 10.01%, and total emissions and steam of 6.67%; main losses: 7.6 kg CO₂ (mixing/fermentation), trim waste 3 kg, exhaust 2.4 kg, steam 1.7 kg (mass imbalance of 0.515 kg due to rounding/evaporation). MFA effectively supports sustainable bakery production through process optimization and waste valorization.